1985
DOI: 10.2343/geochemj.19.113
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of lipid compounds on laboratory heating of a Recent sediment.

Abstract: A lacustrine sediment has been subjected to laboratory heating at 68-325°C for 24h. Various lipid classes were extracted from the unheated and heated sediment samples and analyzed by gas chromato graphy and GC-MS. The compounds recognized include; saturated and unsaturated fatty acids, (3-, co and (w-1)-hydroxy acids, a,w-dicarboxylic acids, fatty alcohols and n-alkanes. The carbon and nitrogen contents and the KMn04 oxidative degradation products (a, w-diacids) of geopolymers (kerogen and humic compounds) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Kawamura and Ishiwatari (1985) found that long chain fatty acids (C12-C32) content of sediment samples heated at 200-325°C for 24h did not decrease. Suzuki and Taguchi (1982) reported that authentic palmitic (C16) and stearic (C18) acids remained unchanged when they were heated alone at 400'C for 20h.…”
Section: Fates Of Organic Acidsmentioning
confidence: 90%
“…Kawamura and Ishiwatari (1985) found that long chain fatty acids (C12-C32) content of sediment samples heated at 200-325°C for 24h did not decrease. Suzuki and Taguchi (1982) reported that authentic palmitic (C16) and stearic (C18) acids remained unchanged when they were heated alone at 400'C for 20h.…”
Section: Fates Of Organic Acidsmentioning
confidence: 90%
“…PROPIONIC BUTYRIC + VALE RIC aliphatic acids with 9 to 30 carbons have been generated from Lake Biwa surface sediments in laboratory heating experiments (Kawamura and Ishiwatari 1985b). Isothermal experiments conducted for 24-h durations generate a steady increase of these acids from 129°C to a maximum at 279 DC, which is followed by a decrease at 300 and 325°C.…”
Section: ~W~--~----~~----~----~----~----~----~~----~--~5~owt%mentioning
confidence: 99%
“…Straight-chain acids with 1 to 32 carbon atoms are the most common acids of this type that are generated from experimentally heated sedimentary organic matter. C12 to C32 acids of this type in surface sediments of Lake Biwa have been monitored through a series of isothermal heating experiments at temperatures from 68 to 325°C for 24-h durations (Kawamura and Ishiwatari 1985b).…”
Section: Saturated Acyclic Aliphatic Monocarboxylic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomarkers preserved in both sample types appear to be useful indicators for identification of an organic-matter (OM) origin Nádudvari et al, 2018). For example, n-fatty acids can serve as useful indicators of OM origin because they are precursors of aliphatic hydrocarbons, which represent some of the main components of petroleum and coal bitumen, which in turn forms via decarboxylation and reduction reactions (Cooper and Bray, 1963;Kawamura and Ishiwatari, 1985;Dong et al, 1993). In addition, n-fatty acids, which are present in recent plant tissues, may be important components of OM involving all types of kerogen.…”
Section: Introductionmentioning
confidence: 99%